The Influence of Investment Value, Micro-Industrial Enterprises and Small Industrial Enterprises on Employment in Sumbagsel in the Perspective of Islamic Economics - Melinda, Gesti Alya; Nurlaili, Nurlaili; Anita, Siska Yuli (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This work aims to analyze the effect of investment value, the quantity of micro-industrial business units and the quantity of small industrial business units on employment in the sumbagsel area in 2019-2023 in the perspective of Islamic economics. In this work, the type of data used is quantitative data. Quantitative Data is data that can be measured and calculated directly, regarding information or explanation in the form of quantitys or statistics. The population used in this work is in 5 provinces in the Sumbagsel Area (Jambi, South Sumatra, Bengkulu, Lampung and Bangka Belitung Islands. The sample used in this work is the province in Sumbagsel Area. In this case, the author uses the sample of the last 5 years, namely 2019-2023. The investment value variable does not significantly affect the employment in Sumbagsel for the period 2019-2023. The variable of Micro Industry Business Unit does not significantly affect the employment in Sumbagsel for the period 2019-2023. Small Industry Business Unit variables do not have a significant effect on employment in Sumbagsel for the period 2019-2023. Investment value variables, micro-industrial business units, and small industrial business units have a significant effect on employment in Sumbagsel for the period 2019-2023. Islamic economic perspective on employment in the perspective of Islamic Economics has a broader dimension than the conventional economic approach.